Global Commodity Chains and the Pandemic - Lara M. Espeter; Patricia Retamal (Journal of World-Systems Research, 2024)
The availability of labor-power is a critical element of all commodity chains. This is especially true of labor-intensive production processes such as agriculture. The COVID-19 pandemic had a major impact on this, as well as on many other aspects of the economy and everyday life. The institutions of the modern world-system responded in various ways to the new situation influenced by COVID-19, taking measures to mitigate and avert the detrimental effects. This paper examines these responses and their impact on the availability of labor-power in the agricultural areas of Nakuru County, Kenya, and O’Higgins Region, Chile. By practically applying world-systems analysis, we shed light on the significance of institutions during periods of stagnation and their impact on the availability of labor-power in global commodity chains. This allows us to draw conclusions about the general impact of institutional responses to stagnation phases at the worker level. We show that the institutions studied responded in very different ways to the stagnation phase affected by COVID-19. As a result, O’Higgins Region experienced a labor-power shortage that Nakuru County had not, which may have a lasting impact on labor-power availability.